Divergent assemblage patterns and driving forces for bacterial and fungal communities along a glacier forefield chronosequence. (March 2018) - Jiang, Yonglei; Lei, Yanbao; Yang, Yan; Korpelainen, Helena; Niinemets, Ülo; Li, Chunyang
Abstract: Despite the ubiquitous distributions and critical ecological functions of microorganisms in pedogenesis and ecosystem development in recently deglaciated areas, there are contrasting successional trajectories among bacteria and fungi, but the driving forces of community assembly still remain poorly resolved. In this study, we analyzed both bacterial and fungal lineages associated with seven different stages in the Hailuogou Glacier Chronosequence, to quantify their taxonomic composition and successional dynamics, and to decipher the relative contribution from the bottom-up control of soil nutrients and altered vegetation as well as top-down pressures from nematode grazers. Co-occurrence networks showed that the community complexity for both bacteria and fungi typically peaked at the middle chronosequence stages. The overlapping nodes mainly belonged to Proteobacteria and Acidobacteria in bacteria, and Ascomycota and Basidiomycota in fungi, which was further supported by the indicator species analysis. Variation in partitioning and structural equation modeling suggested that edaphic properties were the primary agents shaping microbial community structures, especially at the early stages. The importance of biotic factors, including plant richness and nematode feeding, increased during the last two stages along with the establishment of a coniferous forest, eventually governing the turnover of fungal communities. Moreover, bacterial communities exhibited a more compact network topology during assembly, thus supporting determinism, whereas the looser clustering of fungal communities illustrated that they were determined more by stochastic processes. These pieces of evidence collectively reveal divergent successional trajectories and driving forces for soil bacterial and fungal communities along a glacier forefield chronosequence. Highlights: Microbial assembly patterns and their driving forces were studied in a glacier forefield. Microbial community complexity peaked at medium successional stages. Compact clustering of bacteria differed from the looser fungi aring from stochastic processes. Edaphic factors dominated bacterial asseml. Knowledge of soil-plant-microbe-nematode complex provides a holistic view of primary succession.